The influence of two rehabilitation protocols in upper-limb function of stroke patients - Rosa, Marlene (2010)
A significant decrease of upper limb functionality occurs after stroke (Nunes et al., 2005). There are two different approaches on upper limb rehabilitation of stroke patients: unilateral and bilateral protocols (Byblow and Lewis, 2004). The main goal of this study was to assess the differences in the functionality of the hemiparetic upper limb (HUL) among individuals with chronic hemiparesis submitted to a Unilateral Protocol (UP) and those submitted to a Bilateral Protocol (BP). Eight individuals with stroke and chronic hemiparesis were recruited and randomly divided in two groups (four participants in each group). All participants were followed during six weeks and evaluated at four different moments of the intervention protocol using the Fulg-Meyer (FM) Assessment Scale (Fulg Meyer et al. 1975) and the Purdue Pegboard (PP) (Tiffin, 1948). The statistical procedures included percentage evolution and descriptive analysis for each participant. The findings suggest that the UP presented more favorably evolution, considering the FM (9%, 15%, 15%, 0%) and the PP (18%, 8%, --, 10%), when compared with the BP for the FM (0%, -1%, 11%, -22%) and PP (1%, 19%, --, 0%). Therefore, this study suggests that Unilateral Protocols are at least as effective as Bilateral Protocols on hemiparetic upper limb rehabilitation.